Effectiveness of a new combined remedy based on a derivative of dicarbonic acid in conditions of drug-induced hepatitis - Morozyuk, Anastasia; Kudrya, Maria; Melnykivska, Natalya; Ustenko, Nonna; Laryanovska, Yulia (ScienceRise: Biological Science, 2024)
The aim of the study is to evaluate the effect of a new combined remedy based on dicarboxylic acid and a selenium-containing compound on the functional and metabolic state of the liver in conditions of prolonged paracetamol-induced hepatitis. Materials and methods The study was conducted on outbred white rats weighing 200-250 g in compliance with all principles of ethical treatment of animals. Drug-induced liver injury was modeled by oral administration of paracetamol per os for four weeks at a dose of 600 mg per kg body weight. Animals were divided into groups: I - control, which was injected with a solvent (2 % starch solution); II - rats with paracetamol-induced hepatitis; III - rats with hepatitis, which received a new agent based on a dicarboxylic acid derivative and a selenium-containing compound at a dose of 32 mg/kg b.w. Verification of functional and metabolic disorders of the liver was carried out using biochemical methods and histological examination of the liver tissue. Results Significant changes in the activity of hepatic enzymes in animals from the induced hepatitis group compared to intact control animals, increased levels of sialic acids in the blood serum and liver, etc. were recorded. Structural changes in the liver tissue of animals with induced hepatitis were also observed compared to intact control animals. The use of the new remedy led to the normalization of the indicators. Conclusions. In the conditions of paracetamol-induced hepatitis, changes in biochemical parameters in the blood serum and liver homogenate were observed, indicating the development of autoimmune processes in the body. Correction with the new remedy led to the restoration of liver enzyme activity and a decrease in the content of sialic acids in the blood serum and liver homogenate of experimental animals. The new combined remedy based on a dicarboxylic acid derivative and a selenium-containing compound is effective and promising as a potential drug for the correction of liver disorders in the setting of drug-induced hepatitis